Natural organic matter interactions with polyamide and polysulfone membranes: Formation of conditioning film - Gutierrez, L.; Aubry, C.; Valladares Linares, R.; Croue, Jean-Philippe (Elsevier, 2015)
A conditioning film changes the physicochemical properties of the membrane surface and strongly affects subsequent fouling behavior. Results from this Atomic Force Microscopy study indicate that natural organic matter (NOM) characteristics, membrane surface properties, and solution chemistry are fundamental during conditioning film formation. Repulsive forces were observed between HUM (humic-NOM) and polyamide (pa) or polysulfone (PS) membranes during approach in Na+ and Ca2+ solutions. However, repulsive and attractive forces were randomly recorded during BIOP (biopolymer-NOM) approach to both membranes, possibly caused by low electrostatic repulsion, hydrogen bonding, and presence of chemically/physically heterogeneous regions on membrane surfaces. During retracting, Ca2+ ions increased HUM adhesion to PA and PS membrane, indicating cation bridging/complexation as dominant interacting mechanism for this isolate. BIOP adsorption on PS and PA membrane was stronger than HUM under similar solution conditions, where hydrogen bonding would play an important role. Additionally, irrespective of solution conditions, higher adhesion energy was recorded on PS than on PA membrane for both NOM isolates, indicating membrane hydrophobicity as an important interacting factor. Results from this research will advance our understanding of conditioning film formation for NOM isolates and membranes of different physicochemical characteristics.